Roman amphorae in the Trentino-South Tyrol region (Northern Italy): an overview - Maurina, Barbara (Rei Cretariae Romanae Fautorum Acta, 2022)
In the last 20 years archaeological excavations have provided new and significant evidence of the import of pottery in the Trentino – South Tyrol Region (Northern Italy) during the Roman and Late Antique period. In particular, although the material was mostly found in a highly fragmentary state, the evidence of amphora sherds unearthed in urban and rural sites, points out that in this territory from the 1st century BC to the Early Medieval period there was an almost constant demand for essential goods (especially wine, olive oil and fish sauces) usually transported in amphorae and that the region was part of a long distance exchange circuit supplied by seaborne trade. The recorded amphora types are quite numerous and show a provision of foodstuff both from Italy (especially between the 1st century BC and the 2nd century AD) and from different Mediterranean regions (Greece and Spain particularly in the first two centuries AD; North Africa and the Near East especially in the 4th–7th centuries AD). This supply was available thanks to a commercial circuit mainly East oriented through the North-East Adriatic Region, thank to a well developed waterways network connected to the River Adige and a road system based on the via Claudia Augusta. This contribution presents a synthesis of the more recent data on the presence of Roman and late antique amphorae in urban and rural contexts and their meaning for the regional economy.